Gut dysbiosis and multiple sclerosis - Padma, V.; Gaur, Gouri; S., Shobana (International Journal of Advances in Medicine, 2025)
Multiple sclerosis (MS) is a chronic, immune-mediated disorder of the central nervous system marked by multifocal demyelination, neuroinflammation, and progressive neurodegeneration. Globally, it affects about 2.9 million people, creating significant personal, social, and economic burdens. In India, approximately 100,000 to 150,000 individuals live with MS, with prevalence estimates ranging from 8-11 per 100,000 population, and an estimated 6,500 new diagnoses annually. MS imposes a heavy healthcare burden: early diagnosis is often delayed due to low awareness, limited access to neurologists, and inconsistent diagnostic protocols leading to prolonged hospital stay, longer duration of clinically undiagnosed disease and worse overall outcomes. In India, clinical management of MS faces a multitude of challenges in the form of inadequacies in diagnostic ability arising due to lack of advanced training, medical supplies, diagnostic tools and lack of trained neurologists per capita. Additionally, drugs used to manage MS are often expensive and require longer durations of therapy and frequent adjustments on follow up, leading to financial exhaustion for the patient, and subsequently adding to their inaccessibility. In recent years, there has been evidence suggesting a correlation of altered composition of gut commensals with CNS autoimmune diseases like MS. This association opens new avenues for understanding, diagnosing and managing such diseases beyond conventional neurotropic therapy. Any deviation from normal in the gut flora can trigger oxidative damage, that promotes mitochondrial dysfunction, and sets in motion cascades of inflammation via the gut brain axis that eventually led to demyelination and degeneration. Also, various humoral, endocrine and immune connections exist between the gut and brain, that influence release of neurotransmitters, peptides and cytokines that further serve to modify CNS function. This review aims to consolidate evidence that corroborates the link between gut dysbiosis and MS.